2017
DOI: 10.4049/jimmunol.1601912
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase CK2 Controls the Fate between Th17 Cell and Regulatory T Cell Differentiation

Abstract: CK2 is a highly conserved and pleiotropic serine/threonine kinase that promotes many pro-survival and pro-inflammatory signaling pathways including PI3K/Akt/mTOR and JAK/STAT. These pathways are essential for CD4+ T cell activation and polarization, but little is known about how CK2 functions in T cells. Here we demonstrate that CK2 expression and kinase activity are induced upon CD4+ T cell activation. Targeting the catalytic activity of CK2 using the next generation small molecule inhibitor CX-4945 in vitro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(65 citation statements)
references
References 48 publications
3
62
0
Order By: Relevance
“…This was not cell type-dependent, since a CX-4945-induced reduction of pS473 Akt, besides pT308, was repeatedly reported by us and other groups (e.g. [40,[42][43][44][45] and was also observed in C2C12 (S1C Fig) and in GN11 (not shown) cells, where we found that CK2β knock out caused instead an increased pS473 level. The reduction of pS473 by CX-49445 was observed also in shCK2β, suggesting that its increase due to CK2β downregulation requires the presence of active CK2 (see Discussion).…”
Section: Ck2β Depletion In the Renal Cell Line Hk-2 Unbalances P-akt(supporting
confidence: 85%
“…This was not cell type-dependent, since a CX-4945-induced reduction of pS473 Akt, besides pT308, was repeatedly reported by us and other groups (e.g. [40,[42][43][44][45] and was also observed in C2C12 (S1C Fig) and in GN11 (not shown) cells, where we found that CK2β knock out caused instead an increased pS473 level. The reduction of pS473 by CX-49445 was observed also in shCK2β, suggesting that its increase due to CK2β downregulation requires the presence of active CK2 (see Discussion).…”
Section: Ck2β Depletion In the Renal Cell Line Hk-2 Unbalances P-akt(supporting
confidence: 85%
“…In this context, pharmacological inhibition, or genetic silencing of CK2 in CD4 T cells leads to increased Treg generation and decreased Th17 differentiation, possibly as a result of lower STAT3 phosphorylation and the inhibition of the PI3K/AKT/mTOR pathways (Fig. ) . As CK2 is constitutively associated with CD5, the role of CD5 in T cell differentiation has been recently addressed.…”
Section: Cd5 As Regulator Of Th Differentiationmentioning
confidence: 99%
“…Of note, we also detected genes that promote pro-inflammatory T cells. For example, CKS2, LDHA, and LDHB, promote Th17 differentiation ( 83, 84 ), and Th1 T eff cells ( 85 ), respectively. LDHA is induced by T cell activation to support aerobic glycolysis, however, it also promotes IFNγ production via enhanced histone acetylation through acetyl-CoA ( 85 ).…”
Section: Resultsmentioning
confidence: 99%